Euro-zone crisis: Past trends, current developments and perspectives - Mojmir Mrak (Journal of Contemporary Economic and Business Issues, 2014)
After its launching in 1999 and rather successful decade-long performance, the euro-zone entered in 2010 into its first and extremely profound crisis. The crisis has been dragging on for almost four years and there isstill a lot of work to be done in order to reach a comprehensive and sustainable solution. The main objective of the article is threefold. Firstly, to present the main design failures of the original institutional structure of the euro-zone and its economic governance, secondly, to analyze the process of the euro-zone crisis management from its ad-hoc approach in 2010 to a more systematic approach applied over the recent 3 years, and thirdly, to discuss the key elements for a sustainable resolution of the euro-zone crisis. Looking in a more medium-term perspective, the solution of the euro-zone crisis is associated with an appropriate switch of the policy mix it applies. On the long-run, the resolution of the euro-zone crisis depends on the stabilisation of the public finances and, more specifically, on the reduction of the public debt level.
Keywords: F36; G01; G18; 330; euro-zone crisis; crisis management; design failures; prevention mechanism; sustainable resolution